2019
DOI: 10.3390/su11154162
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a Global Citizen through Participation in the Global Storylines Program

Abstract: This study investigates the effect of the Global Storylines educational program which aims to increase primary school students’ sustainability competences and their awareness of global problems. To obtain the data, we organized seven focus groups with a total of 52 students (25 girls, 27 boys) of an average age of 8.55 years, and conducted 7 interviews with 8 teachers (all women). The findings demonstrate the program’s likely effect on students’ improved inter- and intra-personal skills, better social climate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Digital theatre and experiential actions, as well as the use of digital tools and instruments, for example, Google Docs, collaboratively written scenarios based on specific themes, such as sustainable development, climate change, poverty reduction, sustainable consumption, and many others, and then directing and performing scenes could empower students to work collaboratively and interact each other, and as a result discover new knowledge. There seems to be a positive effect in the learning outcomes and by engaging students in the learning process in drama performance they become protagonists of the learning experience by collaborating with their peers [63] and improving their social skills [67]. In this way, they are involved in a diversity of activities, such as script writing, scenery making, directing, and acting, and thus reflect critically about the major environmental problems of our world, trying to propose feasible solutions and practicing higher level thinking skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital theatre and experiential actions, as well as the use of digital tools and instruments, for example, Google Docs, collaboratively written scenarios based on specific themes, such as sustainable development, climate change, poverty reduction, sustainable consumption, and many others, and then directing and performing scenes could empower students to work collaboratively and interact each other, and as a result discover new knowledge. There seems to be a positive effect in the learning outcomes and by engaging students in the learning process in drama performance they become protagonists of the learning experience by collaborating with their peers [63] and improving their social skills [67]. In this way, they are involved in a diversity of activities, such as script writing, scenery making, directing, and acting, and thus reflect critically about the major environmental problems of our world, trying to propose feasible solutions and practicing higher level thinking skills.…”
Section: Discussionmentioning
confidence: 99%
“…Also, they enhance students' motivation, interest, self-reflection, imagination, and creativity of young children and their engagement in the learning process [66]. Similarly, in a qualitative research conducted by [67], the impact of a global storyline program in the creation of sustainability skills and consciousness of primary school students were examined. The findings of this study revealed an improvement in students' personal skills and sensitivity towards environmental problems, and a socially improved class climate.…”
Section: The Digital Technologies and Drama Techniques In Digital Dra...mentioning
confidence: 99%
“…At the product trial stage, students who actively use interactive picture and picture learning media based on articulation storylines experience increased motivation. They convey that the media is easy to use, easy to understand, and the images match their characteristics (Karlsen et al, 2019;Krepelkova et al, 2019;Nurdin et al, 2020;Sukmarini et al, 2021). Interactive picture and picture learning media based on articulate storylines help teachers and provide efficient responses when used (Artika, W., Ratih & Ningtias, 2021;Nissa et al, 2021).…”
Section: Ranksmentioning
confidence: 99%
“…Sustainable development refers to the environment, society and economy, and students are introduced to the interdependence of these three components. The meaning of this topic stems from the awareness that man, through his actions, greatly contributes to natural and global changes (Křepelková et al, 2019). The goals are to gain knowledge about the diversity of nature, to raise awareness of the importance of nature conservation and responsible behavior, to develop empathy towards living beings, to think about the future and one's own actions that will contribute to sustainable development.…”
Section: Sustainable Developmentmentioning
confidence: 99%